Bioprospecção de plantas medicinais Com atividade antimicrobiana e anti-quorum sensing - Portela, Gislaine Simões (2011)
The objective of this research was to investigate the existence of antimicrobial plant compounds and anti-quorum sensing in oral biofilms. The plants used in this study were: Schinus terebinthifolius Raddi (aroeira da praia); Lippia sidoides Scham (alecrim pimenta); Abarema cochiliacarpos (Gomes) B. & J.W. Grimes (barbatimão); Anacardium occidentale Linn (cajueiro); Psidium guajava Linn (goiabeira); Tabebuia avellanedae Lorentz ex Griseb (ipê-roxo); Hymenaea courbaril L. (jatobá) e a Bowdichia virgiloides Kunth (sucupira), Anadenanthera macrocarpa Benth (angico), Abarema cochiliacarpos (Gomes) B. & J.W. Grimes (barbatimão), Ziziphus joazeiro Mart (joazeiro), Sida cordifolia L. (malva branca), Chenopodium ambrosioides L. (mastruz), Punica granatum L. (romã) and Zingiber officinale (gengibre). The extracts were submitted in good yield to the partition with solvents in order of increasing polarity, hexane, dichloromethane and ethyl acetate. The antimicrobial activity was determined by the techniques of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) and use the model QSIs (Quorum Sensing Inhibitor System) proposed by Rasmussen and colleagues (2005). The results proved promising for the development of phytomedicines. The anti-quorun sensing was significant for Abarema cochiliacarpos (Gomes) B. & JW Grimes (barbatimão), Anacardium occidentale Linn (cajueiro), Psidium guajava Linn (goiabeira) and the fruit of Hymenaea courbaril L. (Jatobá). The results support the hypothesis that extracts and partitions of some medicinal plants have anti-quorum sensing activity as a mechanism of antimicrobial activity.